CARNAL SINNERS IN THE SECOND CIRCLE OF HELL IN CANTO V OF DANTE’S INFERNO - Masulah . (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2009)
AbstractThis paper tries to scrutinize Canto V of Inferno, one of the trilogies of Dante’s Devine Comedy. The first section of the paper overviews the general features of Inferno and the general structure of Hell told inInferno. After the general description, the paper then focuses on discussing Canto V which narrates about the carnal sinners in the second circle of Hell. The Carnal sinners are those sinners who abandon themselves to the temptation of lust. It is told in Canto V, that in thesecond circle of Hell, Dante finds the damned spirits of Dido of Cartidge, Helen of Troy, Cleopatra of Egypt and Achilles of Greek. However, in discussing the carnal sinners, it is hardly possible not to discuss Francesca, one of the inmates of the second circle of Hell madeimportant by Dante by telling her adulterous love story elaborately in Canto V. Thus, in the next section, the paper progresses to discussing the predicaments of Francesca’s rhetoric about her love which lead to herdamnation in Hell. It is revealed here that Francesca, cast into hell because of her adulterous love to her brother-in-law Paolo, questions her damnation in Hell. She bases her objection on the idea that her yieldinginto lust is not her fault. It is, she apparently argues, the work of love itself, as an active agent and the romance book she reads, as a stimulating force dragging her into sinful love. This paper tries to reveals that Francesca’s rhetorical justification faults and fails becauseshe annihilates the so-called God’s given free will man innately possesses.